Factors associated with the occurrence of QRS complex alterations obtained by electrocardiography in domestic dogs in Lima, period 2018-2020 - Villar amasifen, Emily (2023)
The objective of the study was to determine the factors associated with QRS complex alterations in domestic dogs undergoing electrocardiographic examination at a cardiological diagnosis center in Lima during the period 2018-2020. An analytical observational study was carried out. A data collection form was used to record information about the dependent variables: duration, amplitude, polarity and morphology of the QRS wave; and the independent variables: age, sex, breed size and obesity of the dog. Subsequently, a logistic regression analysis was performed to quantify the association between the classification variables and QRS complex alterations. The results showed that adult dogs were 1.74 times more likely to present QRS complex lengthening, and geriatric dogs were 2.14 times more likely to present alterations in the duration of this electrocardiographic variable compared to young dogs. . On the other hand, geriatric dogs were 0.17 times less likely to have a negative QRS complex and adult dogs were 0.16 times less likely to have alterations in the polarity of this complex than young dogs. It is concluded that age has been the main factor associated with alterations in the duration of the QRS complex in domestic dogs undergoing electrocardiographic examination.